Kreativitas Guru Dalam Meningkatkan Kualitas Pembelajaran - Arsalam Arsal; Mirwan Rasyadi Wannn; Roihan Al Fadhil; Sam'un Mukramin (Jurnal Pendidikan Dasar Islam, 2023)
Teachers can support the quality of learning taught, mastery of the material, and mastery of the learning process. This study aims to determine teacher creativity in improving learning at SMPN 4 BONTONOMPO. This research took a qualitative approach. The descriptive nature of this research makes teachers' creativity very visible. Data collection in this study includes interviews and observations, documentation studies and data analysis including data classification, data reduction, data description, and conclusions. The results of this study show that there are four key components in the development of this qualitative research related to teacher creativity in improving the quality of learning at SMPN 4 BONTONOMPO, such as teacher creativity in understanding the learning material to be taught, creativity in managing the classroom environment, creativity in the use of various learning methods and teacher creativity in the use of learning media.